MULTI-MODEL VARIATION OF THE ENHANCED ASIAN RAINFALL AND CONTINENT-OCEAN THERMAL GRADIENT FROM PRE-INDUSTRIAL TO MID-HOLOCENE - Adinda Maharani; Yudha Setiawan Djamil; Rima Rachmayani (Marine Geological Institute of Indonesia, 2022)
Rainfall over the Asian continent during the mid-Holocene was higher than today as shown by the rainfall proxy records. During the mid-Holocene, increased rainfall over the Asian Continent has been suggested to be associated with the strengthening of the Asian Summer Monsoon (ASM) following a sharper continent-ocean thermal gradient. This study examined multi-model variation between changes of the continent-ocean thermal gradient and the increased rainfall over Asia during the mid-Holocene as compared to the pre-Industrial. We analyzed surface temperature, precipitation, and wind at 850mb from nine Global Climate Models (GCMs) which are all obtained from the database of the Paleoclimate Modeling Intercomparison Project Phase-3 (PMIP3). Multi-model analysis shows that changes in a continent-ocean thermal gradient has a positive correlation with ASM wind. However, a negative correlation occurs between changes in the continent-ocean thermal gradient with Asian rainfall. Models that simulate large changes in the continent-ocean thermal gradient produced the smallest increase in the Asian rainfall and vice versa. Such inverse relation is likely due to the cooling of Indian Ocean SST since its correlation scores with Asian rainfall is much higher than the one with the warming of the Asian continent. Thus, multi-model variation of the increased rainfall over the Asian continent between mid-Holocene and today is mainly related to the multi-model variation of the cooling in the Indian Ocean SST.